Dissimilar Rotary Friction Welding of Inconel 718 to F22 Using Inconel 625 Interlayer - Ateekh Ur Rehman (MDPI AG, 2021)
Dissimilar metal joining has always been a challenging task because of the metallurgical incompatibility and difference in melting points of alloys being joined. Diffusion and mixing of alloying elements from dissimilar base metals at the weld often cause unwanted metallurgical changes resulting in unsuccessful welds or underperformance of the weldment. Solid-state dissimilar friction welds of Inconel 718 and F22 were prepared in this study with an Inconel 625 interlayer to address the carbon enrichment of Inconel 718 during the welding. Defect-free rotary friction welds were produced in this study. Microstructural and mechanical properties investigation of the weldments and base metals was carried out, and results were analysed. Intermixing zone was observed at the weld interface due to the softening of the metal at the interface and rotatory motion during the welding. The high temperatures and the plastic deformation of the intermixing zone and thermo-mechanically affected zone (TMAZ) resulted in the grain refinement of the weld region. The highest hardness was observed at the Inconel 718/F22 weld interface due to the plastic strain and the carbon diffusion. The tensile specimens failed in the F22 base metal for the weld prepared with and without the Inconel 625 interlayer. Inconel 718/F22 welds exhibited lower toughness values compared to the Inconel 718/F22 welds prepared with Inconel 625 interlayer.